Integrated Geophysical Assessment of Groundwater Potential in Southwestern Saudi Arabia - Mohamed, Ahmed; Al Deep, Mohamed; Othman, Abdullah; Taha, Ayman I.; Alshehri, Fahad; Abdelrady, Ahmed (Frontiers in Earth Science, 2022)
Saudi Arabia is seeking fresh groundwater resources to face the increase in anthropogenic activities. The groundwater storage variations and occurrence were investigated and the surface and subsurface structures influencing the groundwater resources in the research area were defined using a combined study of Gravity Recovery and Climate Experiment, aeromagnetic data, and electrical resistivity data with other relevant datasets. Results are: The groundwater storage fluctuation is calculated at −0.34±0.01 mm/yr during the period 04/2002-12/2021. The area is receiving an average annual rainfall rate of 117.6 mm during the period 2002 to 2019. Three structural trends, defined in the directions of NS, NNW, and NNE are cutting the sedimentary cover and the basement rocks. The sedimentary cover ranges from 0 to 1.2 km thick. VES results indicate three main geoelectric layers: the surface geoelectrical layer of higher resistivity values (428-9626 Ohm.m) is made up of unconsolidated Quaternary sediments; the water-bearing layer of saturated sands with a resistivity range between 5.1 and 153 Ohm.m and with depths vary from 1 to 94 m, and highly fractured basement rocks with resistivity values ranging from 813 and 6125 Ohm.m. The integrated results are useful in providing a comprehensive image of the study area's surface and subsurface structures, as well as groundwater potential in the southwestern part of Saudi Arabia. Our integrated approach provides a reproducible model for assessing groundwater potential in arid and semiarid areas.